War drama as a living reality - Briukhovetska, Larysa (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2023)
Since 2014, the Russian aggression in Ukraine has prompted filmmakers to master a new genre of war drama to tell the stories of those who serve in the Ukrainian army or the territorial defense, as well as those who contribute to the war effort as volunteers. The article discusses Ukrainian war drama films: Cyborgs. Heroes Don’t Die, Call Sign Banderas, Mother of Apostles, Ilovaysk 2014. Donbas Battalion, Sniper. The White Raven. These films integrate war drama with other genres such as detective stories, adventure films, and psychological drama. They also refer to some archetypal themes and conflicts in order to frame the current experience of the war. However, it will be argued that these films do not simply reuse the existing genre models, but complicate them. They refresh war drama by prioritizing the concrete experience of the ongoing war against Russian aggression over the genre conventions. Ukrainian war drama shows not a game of war but the truth of war. It tells the real stories of the bravery of ordinary people who fight against Russian aggression.